Leadership, Work Load, Work Environment, And Additional Employee Income (TPP) Its Influence On State Civil Apparatus (ASN) Performance In The Health Service Of Ogan Ilir Regency - Tien Yus Tini; Rita Sawalina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of leadership, workload, work environment, and employee income allowance (TPP) on the performance of Civil Servants (ASN) at the Health Office of Ogan Ilir Regency. A cross-sectional design was employed with a total sample of 104 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression tests to identify the influence of independent variables on the dependent variable. The results revealed that, partially, leadership significantly affects ASN performance (p = 0.020). Workload also significantly influences ASN performance (p = 0.003). The work environment contributes significantly to ASN performance (p = 0.015), as does TPP (p = 0.017). Simultaneously, the four independent variables leadership, workload, work environment, and TPP have a significant impact on ASN performance, as indicated by an F-test significance value of 0.000 (p < 0.05). The Adjusted R Square value of 0.299 indicates that 29.9% of the variation in ASN performance is explained by these four variables, while the remaining is influenced by other factors beyond this study model. This study highlights the importance of effective leadership, balanced workload, a conducive work environment, and adequate employee income allowances in improving ASN performance. Recommendations are provided for policymakers to consider these factors in efforts to enhance ASN performance in the health sector.